Identifikasi Kesalahan Penyelesaian Masalah Konsep Himpunan pada Siswa Kelas VII SMP Negeri 15 Mataram - Farizal Wahyu Trigantara; Amrullah Amrullah; Syahrul Azmi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2022)
The sets concept that still be the problems for students of class VII at SMPN 15 Mataram. The average of daily test score on the material sets of students of class VII is 60.45 with 38.81% of classical completeness. It means that most of seventh grade students make mistakes in order to complete the daily test questions related to the concept of the sets. The aim of this research is to identify an error to solve the question of sets by students of seventh grade at SMPN 15 Mataram in academic year 2017/2018. In addition, this study is conducted to determine the level of error to solve about the sets material, and to see the relationship of every types of error with the overall error in order to solve the question of sets. The type of this research is descriptive research of quantitative type. The data analysis technique used in this research is statistical descriptive data analysis and correlation analysis of pearson product moment test. The result of the research shows that the dominant error of students is the type of error using theorem, definition, or formula with error percentage 56.19%. Based on the basic competence of the sets material, students make the most mistake on basic competence 4.5 with percentage of error of 61.71%. In addition, the type of error using the data is stronger relation with a correlation coefficient 0.89 which is very strong category.